The Philosophy of Christian Religious Education - Astley, Jeff (Birmingham Religious Education Press, 1994)
0-89135-093-4This book has been written with the intention that it should be useful to, and therefore usable by, Christian religious educators of widely differing theological and educational outlooks. Part I offers some introductory material about the nature of Chri
Keywords: Christian education -- Philosophy. Religious education -- Philosophy. Godsdienstige opvoeding